A Systematic Literature Review on the Effectiveness of Distance Learning: Problems, Opportunities, Challenges, and Predictions - Kusmaryono, Imam; Jupriyanto, Jupriyanto; Kusumaningsih, Widya (International Journal of Education, 2021)
Distance learning has increased in popularity during the COVID-19 pandemic as a new method for research and learning. However, the implementation of distance learning with management learning systems still faces a problem, namely the difficulty of understanding instructional objectives. Regardless of the pros and cons, the results of literature research suggest that distance education is as effective as face-to-face (traditional) learning in terms of student learning outcomes. The application of distance learning (online learning) has many opportunities to develop rapidly as most academic institutions shift to this model. Improving the quality of distance learning programs poses a real challenge in developing challenging content that does not only cover the curriculum but is also engaging. It is strongly predicted that the application of distance learning will not only be part of the normal learning process but will completely replace the current face-to-face conventional teaching and learning.